Analysis Live Streaming and Online Consumen Reviews in Influencing Purchase Intention on Social Commerce Platforms - Ahmad Prayugo; Ratna Roostika (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The development of social commerce has presented a new way of buying and selling activities through the integration of interactive features such as live streaming and online consumer reviews (OCR). This study aims to analyze the combined effect of live streaming components consisting of sense of community, interactivity, and emotional support and OCR consisting of perceived usefulness and perceived trust on customer engagement and consumer purchase intention on the TikTok Shop platform. This study uses a quantitative approach with a survey method distributed via Google Form to 231 respondents in Indonesia using convenience sampling techniques. Data were analyzed with Partial Least Square-based Structural Equation Modeling (PLS-SEM). The results showed that most of the independent variables had a significant effect on customer engagement and purchase intention, and customer engagement proved to be a strong mediating variable in shaping consumer purchase intention. These findings support the channel complementarity theory, which states that consumers utilize various information channels simultaneously to meet their information needs. This research provides theoretical contributions to the development of social commerce studies as well as practical implications for businesses in designing more effective marketing strategies through the combination of live streaming and online consumer reviews.